IS ONLY REQUESTING AN ANTI-HCV TEST SUFFICIENT FOR HEPATITIS C SCREENING? - Rabia Deniz; Seda Karslı; Ömer Burak Ekinci; Ilkane Kalantarova; Alp Atasoy; Mustafa Önel; Ali Ağaçfidan; Filiz Akyüz; Kadir Demir; Fatih Beşışık; Sabahattin Kaymakoğlu (İstanbul Tıp Fakültesi Dergisi)
Objective: Unless treated, a hepatitis C virus (HCV) infection is associated with high morbidity and mortality. The study investigates anti-HCV screening efficacy and treatment access rates for patients.Material and Method: This cross-sectional study screened all anti-HCV tests requested between January 2014-June 2017 from hospital records. Patient interviews were conducted by telephone-based interview. Result: The overall number of anti-HCV tests requested was 77,783, 1,373 of which were positive. Among these, the study interviewed 488 patients (266 females, 222 males; mean age=52.81±16.5 years) and analyzed their tests. Further investigation with HCV-RNA had not been done in 69 (14.1%) anti-HCV positive patients. HCV-RNA was positive in 309 patients, 268 of whom were treated (86%), while 41 were not (14%). The main reasons for remaining untreated are: unknown (21%), no patient follow up (28%), or physician didn’t indicate (19%). Conclusion: In order to successfully eliminate HCV, the anti-HCV test alone is not enough. Informing patients about the results of the anti-HCV test and, if positive, referring them for the HCV-RNA test are important. When considering the high amount of untreated patients, linkage to care should be encouraged in HCV-RNA positive patients unless an absolute contraindication is present.